ANALYSIS OF BILATERAL COOPERATION OF REPUBLIC OF KOREAN AND INDONESIA TO DEVELOPING KOREAN’S HALAL INDUSTRY - Rayi Adita Sabrina (Mediasi: Journal of International Relations, 2020)
The development of Korean Wave or Hallyu around the world gave rise to the phenomenon of bilateral cooperation between South Korea and Indonesia in the development of halal industry which is currently a popular issue in the international industry and has improved the economy in the field of industry with the concept of halal. To develop the Korean halal industry, Korea needs to conduct bilateral diplomacy and halal certification to improve the development of the Korean halal industry that is guaranteed halal. This study discusses the bilateral relationship between the Republic of Korea and Indonesia in the development of the Korean halal industry. The analysis used in this study to answer the focus of the problem is how is the strategy of Korea and Indonesia in the development of the Korean halal industry?. With the cooperation of Korea and Indonesia can know the strategy issued by Korea in developing the Korean halal industry, namely through the Korean Muslim Federation (KMF) and the Indonesian Ulema Council (MUI) and the cooperation of the Government of South Korea with several halal certification institutions to enter the competition in the Halal market industry (Global Halal Market). South Korea's efforts in promoting themselves as a Muslim Friendly Country and knowing the potential of increasing the halal market in Indonesia. Bilateral cooperation established by the two countries has been able to improve the country's economy in the field of industry. South Korea also received a positive response in expanding its halal market and increasing investment in Indonesia. Thus, bilateral cooperation conducted by the two countries to meet the national interest is not influenced by the religious background factor of a country. It is precisely the interest factor in improving the country's economy that plays an important role in cooperation relations.Keywords: South Korea, Indonesia, Halal Industry, Bilateral Cooperation